Radiation interference from sources rotating around Schwarzschild black holes - Mendes, Raissa F. P. [UNESP]; Matsas, George E. A. [UNESP] (American Physical Society (APS), 2011)
We investigate the influence of the spacetime curvature on the interference of the radiation emitted by an ensemble of scalar sources in circular motion around a Schwarzschild black hole. We pay particular attention to the transition from the radiating to the nonradiating regime as the number of sources increases. © 2011 American Physical Society.